The pi-helix formation between Asp369 and Thr375 as a key factor in E1-E2 conformational change of Na+/K+-ATPase - Tejral, G; Koláčná, L; Schoner, W; Amler, E (Physiological research, 2009)
Molecular modeling of the H4-H5-loop of the alpha2 isoform of Na+/K+-ATPase in the E1 and E2 conformations revealed that twisting of the nucleotide (N) domain toward the phosphorylation (P) domain is connected with the formation of a short pi-helix between Asp369 and Thr375. This conformational change close to the hinge region between the N-domain and the P-domain could be an important event leading to a bending of the N-domain by 64.7 degrees and to a shortening of the distance between the ATP binding site and the phosphorylation site (Asp369) by 1.22 nm from 3.22 nm to 2.00 nm. It is hypothesized that this shortening mechanism is involved in the Na+-dependent formation of the Asp369 phospho-intermediate as part of the overall Na+/K+-ATPase activity.
Keywords: sodíko-draslíková ATPasa; threonin; Models, Molecular; protein - isoformy; Protein Isoforms; Sodium-Potassium-Exchanging ATPase; Kinetics; Aspartic Acid; kyselina asparagová; vazebná místa; sekundární struktura proteinů; Protein Structure, Secondary; molekulární modely; kinetika; Binding Sites; Threonine